A Study on Home Safety Practices to Prevent Childhood Injuries Among Mothers - Avabratha Kadke, Shreedhara; Chunduri, Sujatha; Shenoy Kudpi, Varadaraj (Journal of Nepal Paediatric Society, 2020)
Introduction: Most unintentional injuries in children occur at home and many are preventable. Mothers and family’s role in injury prevention is very important. We intended to study the role of home safety practices in prevention of childhood injuries. Methods: This descriptive cross-sectional study was done using a questionnaire. Mothers of children aged one to five years were assessed about home safety practices to prevent childhood injuries. Questionnaire included personal data about the participants such as age, occupation, education, family size and number of children. Safety practices followed by mothers to prevent six types of injuries namely burn, cut, fall, drowning, poisoning and choking were noted. Results: Of the 150 mothers interviewed, 104 were aged below 30 years, 88 were educated up to high school and 130 were housewives. Thirty mothers reported some kind of injury sustained by their children, of which twenty-one were falls. Among precautionary measures mother – behaviour safety initiatives e.g. checking the hot water temperature (88%) or not leaving child alone (92%) got better responses than passive or environmental modifications e.g. using electrical – outlet protection (44%), staircase gates (52%). Overall safety practices were reasonably good with the majority scoring above 50%. Age, education, number of children, occupation of the mother, child age and history of injury did not correlate with the level of safety practices. Conclusions: Mothers’ home safety practices to prevent childhood injuries were relatively better in majority of the study population. Mother’s age, educational level, occupation, number of children, child’s age and history of injury did not affect how mother and her family practiced safety measures.